Association between Age and Histopathological Grade of Bladder Urothelial Carcinoma - Dionisius Alby; Abdul Hadi Hassan; Jupiter Sibarani (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Bladder cancer, particularly urothelial carcinoma, is prevalent in male and ≥55 years old population. Grade of the bladder tumor affects clinical characteristics, management, and prognosis of the patient. This study aimed to analyze the association between age and histopathological grade of bladder urothelial carcinoma. Methods: This cross-sectional analytical study was approved by the Ethical Clearance Committee of Dr. Hasan Sadikin General Hospital, involving 241 medical records of bladder urothelial carcinoma patients in the Department of Anatomical Pathology at Dr. Hasan Sadikin General Hospital during 2009–2013. Chi-square test was applied to 45 patients with complete record of histopathological grade.Results: Most of the subjects were 65 years old. Male patients were the most frequent. The proportion of low-grade carcinoma in <65 years old age group was only 39.1%, while in ≥65 years old age group was 72.7%. The proportion of high-grade carcinoma in <65 years old age group reached 60.9%, which was 27.3% higher than in ≥65 years old age group. Chi-square test result showed a statistically significant difference between histopathological grade of urothelial carcinoma in <65 years and ≥65 years age groups (p=0.023).Conclusions: Proportion of high-grade and low-grade urothelial carcinoma between <65 years and ≥65 years age groups are statistically different; therefore, an association between age and histopathological grade of bladder urothelial carcinoma is shown.